Genetic associations between ULK3 and epilepsy: a two-sample Mendelian randomization study - Liu, Baolai; Fan, Keyi; Zheng, Xinyi; Zhang, Yaochen; Bai, Shangkai; Liu, Zhentong; Xu, Shuhan; Su, Zhihao; Cao, Huiting; Zhang, Heyi; Zhang, Shengxiao (Frontiers in Neurology, 2024)
Background and Objectives: Observational studies have suggested that a multitude of pathological processes and biomolecules are involved in the initiation and development of epilepsy, and ULK3 is linked to the nervous system. However, it remains uncertain whether this association between ULK3 and epilepsy is causal and the direction of any causal relationship. This study employs a two-sample Mendelian randomization (MR) method to investigate the relationship between ULK3 and the risk of epilepsy.Methods: We analyzed genome-wide association study (GWAS) summary statistics for ULK3 (sample size = 3,301), focal epilepsy (sample size = 39,348), and generalized epilepsy (sample size = 33,446). Bidirectional MR analyses were conducted to explore these relationships. We selected a set of single nucleotide polymorphisms (SNPs) with an association threshold of less than 1×10 -5 as instrumental variables for further analysis.Various MR methods, including Inverse Variance Weighted, Weighted Median, MR-Egger Regression, Simple Model, Weighted Model, and Robust Adjustment Profile Score were used. Sensitivity analyses were performed to ensure the robustness of the results.Results: Our MR analyses revealed a causal relationship where an increased level of ULK3 was associated with a decreased risk of focal epilepsy (odds ratio = 0.92, 95% confidence interval: 0.86-1.00, p = 0.041). No significant heterogeneity (Q = 7.85, p = 0.165) or horizontal pleiotropy (Egger regression intercept = 0.0191, p = 0.415) was detected. However, in the reverse analysis, we found no significant causal effect of focal epilepsy on ULK3 (p > 0.05). Furthermore, no significant causation was identified between ULK3 and generalized epilepsy (p > 0.05).This study suggests a causal relationship between ULK3 and the risk of focal epilepsy from a genetic perspective. Nevertheless, further investigation is needed to understand the role of ULK3 in epilepsy fully.